2003
DOI: 10.1080/1352816031000074973
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of machining parameters of Wire-EDM based on Grey relational and statistical analyses

Abstract: terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, re-distribution, re-selling, loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden.The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of any instructions, formulae and drug doses should be independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
100
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(104 citation statements)
references
References 7 publications
2
100
0
2
Order By: Relevance
“…The conclusion was that the discharge current, pulse duration, dielectric flow rate and the interaction between discharge current and pulse duration were more significant parameters for cutting operation. [4] Tosun&Cogun in 2003 in their investigation on AISI 4140 steel using regression analysis concluded that the wire wear ratio increases with increase in pulse duration and open circuit voltage while decreases with increase in wire speed and dielectric fluid pressure. [5] Singh &Gargin 2009 investigated the effect of various process parameters of WEDM like pulse-ontime, pulse-off-time, servo voltage, peak current, wire feed, and wire tension on hot die steel using one variable at a time approach.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion was that the discharge current, pulse duration, dielectric flow rate and the interaction between discharge current and pulse duration were more significant parameters for cutting operation. [4] Tosun&Cogun in 2003 in their investigation on AISI 4140 steel using regression analysis concluded that the wire wear ratio increases with increase in pulse duration and open circuit voltage while decreases with increase in wire speed and dielectric fluid pressure. [5] Singh &Gargin 2009 investigated the effect of various process parameters of WEDM like pulse-ontime, pulse-off-time, servo voltage, peak current, wire feed, and wire tension on hot die steel using one variable at a time approach.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, machining parameters are selected manually based on the engineer and operator experiences [3]. The selection of parameters in order to obtain the optimum machining performances is very complex due to the best parameter combination is unknown especially to the beginners and non machining expertise.…”
Section: Introductionmentioning
confidence: 99%
“…J.T. Huang et al [11] performed optimization of machining parameters of wire EDM based on grey relational and statistical analysis. An improved percentage of 11.69% for machining performances was obtained by applying the proposed approach.…”
Section: Introductionmentioning
confidence: 99%